Trichia decipiens - Krivomaz, Т. І.; Michaud, A.; Minter, D. W. (CABI, 2012)
Diagnostic features. This species is easily recognised by the shining, olivaceous and membranous peridium and translucent stalk filled with spore-like cysts. No other stalked species of Trichia has both of these features.
Keywords: myxomycetes; міксоміцети; Trichia decipiens